Perceptions of farmers and government officials towards the effects of air pollution on honey bees in Bhutan - Sharma, Govinda Prasad; Sapkota, Ramesh Prasad; Gurung, Tulsi; Puppala, Siva Praveen; Maskey Byanju, Rejina (Nepal Journal of Environmental Science, 2026)
Bees interact with the environment, mainly the atmosphere, during foraging, and collect a wide range of airborne suspended particulate matter. Integrating beekeeping into farming operations is an important initiative for improving livelihoods, but little is known about the perceived impacts of air pollution on honey bees in Bhutan. This study aims to examine the perspectives of Bhutanese farmers and Department of Livestock (DOL) officials on the effects of air pollution on honey bees. PM2.5 concentrations of Thimphu from 2018 to 2024, collected by the National Environment Commission (NEC) and made available by the National Statistical Bureau (NSB) were utilised for the data analysis. Questionnaire survey was undertaken from 85 farmers and 85 DOL officials to acquire information on air pollution and its impact on bees. Between 2018 and 2024, PM2.5 concentrations revealed a twofold rise, with levels above the WHO 2021 Air Quality Guidelines (AQG) of 5 µg/m³, indicating a continual worsening in the quality of the air in Thimphu as well as in Bhutan. Almost 55% of farmers and DOL officials reported an increase in air pollution, while 48% indicated a decline in Bhutan's bee populations over time. It was found that 77% of the respondents felt that bees and bee products are negatively impacted by air pollution. Similarly, 61% believe that apiculture will reduce rural-urban migration in Bhutan. Re-enforcing current laws and regulations is necessary to reduce air pollution and its impacts on honey bees in Bhutan.